Dynamic Interactions of Technological Innovations on Sustainable Production and EF - Žun, Štefan (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
We discuss the impact of technological innovations in shaping sustainable production and assessing ecological footprints in Slovenia, recognizing the need for a more critical assessment of the impact of sustainable production on the assessment of ecological footprints (impacts on the environment). Increased use of natural resources and economic growth increase ecological footprints, while technological innovations contribute to reducing negative environmental impacts. Slovenia achieves an innovation index of 84.9% (2020) in the field of innovation and aims to achieve a value of 110% by 2030 compared to the EU average. Slovenia's ecological footprint indicator in 2020 is 4.78 gha, which is 102.7% of the EU average and has been declining since 2008, weakly indicating confirmation of the hypothesis of the environmental Kuznetsov curve. We estimate that research in this area does not provide accurate results (the study of the social environment is missing), taking into account the fact that any activity aimed at resource use and technological innovation can significantly change ecological footprints. Our key findings lead to an awareness of the importance of innovation for achieving sustainable production and, consequently, reducing ecological footprints.